2014
DOI: 10.1517/14728214.2014.914171
|View full text |Cite
|
Sign up to set email alerts
|

Emerging drugs and combination strategies for basal cell carcinoma

Abstract: BCCs typically regress during therapy with Hh inhibitors. Muscle toxicity, dysgeusia and hair loss can be considered as on target adverse reactions. Muscle toxicity is the dose-limiting toxicity of sonidegib. It was not seen with vismodegib because of its high binding to plasma protein α-1-acid glycoprotein. Sonidegib is different and shows a clear dose-toxicity relationship, which allows to address the question of whether there is a dose dependency of regression rate, cure rate and progression-free survival. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 89 publications
0
14
0
Order By: Relevance
“…Vismodegib has been shown to achieve significant tumor regressions including complete responses in locally advanced and metastatic BCC [5,20,21,22]. The rate of low-grade adverse events (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Vismodegib has been shown to achieve significant tumor regressions including complete responses in locally advanced and metastatic BCC [5,20,21,22]. The rate of low-grade adverse events (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, SMO antagonism is proposed to be a potential therapeutic strategy for these cancers. Various Hh signal inhibitors targeting SMO have been investigated in clinical trials; of these, vismodegib showed good efficacy in clinical trial and was approved as the first Hh pathway inhibitor for treating advanced BCC (Amakye et al, 2013;Basset-Seguin et al, 2015;Dreier et al, 2014). Sonidegib, another SMO antagonist, also exhibited antitumor activity in advanced BCC and relapsed medulloblastoma with an acceptable safety profile (Dreier et al, 2014;Migden et al, 2015;Rodon et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Of 9 patients, who were resistant to vismodegib, all were treated with sonidegib and 5 experienced disease progression, three experienced stable disease, in one case response was not evaluable 36 . This, in addition to detection of intra-tumor heterogeneity of resistance mechanisms, suggests that other approaches (itraconazole, arsenic trioxide, IFN α-2b) or new SMO inhibitors (LEQ 506, XL139, Taladegib, TAK-441) could be needed to overcome resistance 24,35 .…”
Section: Atwood Et Al Identified That In Presence Of Vismodegib Smmentioning
confidence: 99%
“…Possible treatment combinations have been discussed earlier 24 . However, based on the impact of Hh inhibition on the immune privilege of BCC, combinations with immunostimulants such as interferon, imiquimod or checkpoint inhibitors appear promising and realistic also in the context of the known adverse reaction profiles.…”
Section: Expert Opinionmentioning
confidence: 99%
See 1 more Smart Citation